Effects of nano-engineered surfaces on osteoblast adhesion, growth, differentiation, and apoptosis. Issue 1 (March 2020) - Miralami, Raheleh; Sharp, John G; Namavar, Fereydoon; Hartman, Curtis W; Garvin, Kevin L; Thiele, Geoffrey M
Modifying implant surfaces to improve their biocompatibility by enhancing osteoblast activation, growth, differentiation, and induction of greater bone formation with stronger attachments should result in improved outcomes for total joint replacement surgeries. This study tested the hypothesis that nano-structured surfaces, produced by the ion beam-assisted deposition method, enhance osteoblast adhesion, growth, differentiation, bone formation, and maturation. The ion beam-assisted deposition technique was employed to deposit zirconium oxide films on glass substrates. The effects of the ion beam-assisted deposition technique on cellular functions were investigated by comparing adhesion, proliferation, differentiation, and apoptosis of the human osteosarcoma cell line SAOS-2 on coated versus uncoated surfaces. Ion beam-assisted deposition nano-coatings enhanced initial cell adhesion assessed by the number of 4′, 6-diamidino-2-phenylindole–stained nuclei on zirconium oxide nano-coated surfaces compared to glass surfaces. This nano-modification also increased cell proliferation as measured by mitochondrial dehydrogenase activity. Moreover, the ion beam-assisted deposition technique improved cell differentiation as determined by the formation of mineralized bone nodules and by the rate of calcium deposition, both of which are in vitro indicators of the successful bone formation. However, programmed cell death assessed by Annexin V staining and flow cytometry was not statistically significantly different between nano-surfaces and glass surfaces. Overall, the results indicate that nano-crystalline zirconium oxide surfaces produced by the ion beam-assisted deposition technique are superior to uncoated surfaces in supporting bone cell adhesion, proliferation, and differentiation. Thus, surface properties altered by the ion beam-assisted deposition technique enhanced bone formation and may increase the biocompatibility of bone cell–associated surfaces.